The natural occurrence, toxicity mechanisms and management strategies of Fumonisin B1：A review. (1st March 2023) - Gao, Zhicheng; Luo, Kangxin; Zhu, Qiuxiang; Peng, Jinghui; Liu, Chang; Wang, Xiaoyue; Li, Shoujun; Zhang, Haiyang
Abstract: Fumonisin B1 (FB1) contaminates various crops, causing huge losses to agriculture and livestock worldwide. This review summarizes the occurrence regularity, toxicity, toxic mechanisms and management strategies of FB1. Specifically, FB1 contamination is particularly serious in developing countries, humid and hot regions. FB1 exposure can produce different toxic effects on the nervous system, respiratory system, digestive system and reproductive system. Furthermore, FB1 can also cause systemic immunotoxicity. The mechanism of toxic effects of FB1 is to interfere with the normal pathway of sphingolipid de novo biosynthesis by acting as a competitive inhibitor of ceramide synthase. Meanwhile, the toxic products of sphingolipid metabolic disorders can cause oxidative stress and apoptosis. FB1 also often causes feed contamination by mixing with other mycotoxins, and then exerts combined toxicity. For detection, lateral flow dipstick technology and enzyme linked immunosorbent assay are widely used in the detection of FB1 in commercial feeds, while mainstream detection methods such as high performance liquid chromatography and liquid chromatography-mass spectrometry are widely used in the laboratory theoretical study of FB1. For purification means of FB1, some natural plant extracts (such as Zingiber officinale and Litsea Cubeba essential oil) and their active compounds have been proved to inhibit the toxic effects of FB1 and protect livestock due to their antifungal and antioxidant effects. Natural plant extract has the advantages of high efficiency, low cost and no contamination residue. This review can provide information for comprehensive understanding of FB1, and provide reference for formulating reasonable treatment and management strategies in livestock production. Graphical abstract: Image 1 Highlights: FB1 exposure is more common in humid and hot regions of developing countries. FB1 exposure causes multisystem toxic effects and systemic immunotoxicity in animals. FB1 induces sphingolipid metabolism disorders, oxidative stress and apoptosis. FB1 toxicity mechanisms are regulated by JNK, TNF-α and Bcl-2/Bax pathways. Natural plant extracts can alleviate the FB1 toxicity, which has a research prospect.